"Das eigentliche Problem vom Menschen": Debt, (Ac)Countability, and the Financialization of Wildlife Conservation. Issue 2 (3rd April 2021) - Driscoll, Kári
Abstract: In 2019, a new strategy in wildlife conservation was announced: so-called "rhino impact bonds, " designed to support the conservation of African black rhinos, with the ultimate aim of establishing a global "conservation debt market." This essay takes this development in the financialization of wildlife conservation as an object lesson in the mutual imbrication of guilt, debt, and the (non)human in the age of the Anthropocene. To this end, it traces a theoretical trajectory that explicitly frames the figure of "Man" in terms of Schuld, starting with Nietzsche's Genealogy of Morals . The essay takes Nietzsche's "sovereign individual" to refer not to the human species as a whole but rather a specific "genre" of the human, namely what Sylvia Wynter calls homo oeconomicus . In "overrepresenting" himself as the paradigmatic human, this figure has established capital accumulation as the goal of all human life. From here, the essay turns to Walter Benjamin's characterization of capitalism as a religion whose ultimate aim is not salvation but universal debt/guilt, and finally to Adorno's account of nature conservation as domination. The rhino bonds represent the logical consequence of this trajectory, namely the expansion of the principle of universal debt to the entire natural world.